Implementing community renewables: institutional work in South Africa's renewable energy procurement programme - Wlokas, Holle Linnea (Energy Research Centre, 2018)
In 2014, for the first time in its history, South Africa fed the national electricity grid with electricity generated through utility-scale renewable energy projects. The Renewable Energy Independent Power Producer Procurement Programme (REIPPPP) is the policy instrument driving this change. The process requires bidding private energy companies to commit resources in alleviation of local socio-economic needs. This thesis analyses the question how the institutions evolve in the implementation of community benefit requirements. The theoretical frameworks of institutional work and logics helps to analyse this new organizational field and interaction of various actors in government, industries and communities. An action research approach grounds this research empirically and aims to create the opportunity for actors to reflect on their actions and engagement in the community benefit implementation process. The research asks how are government, companies and communities shape institutions in the implementation of the community benefit requirements in South Africa's REIPPPP? The study first analyses the procurement requirements for community benefit and ownership, then, secondly, reviews the first 64 approved project bids for suggestions made in response to these requirements. A third research step involves fieldwork in 13 wind and solar projects across the country, the fieldwork consisting of interviews with project stakeholders about their experiences. The research negotiates access to an emerging and competitive, but also enquiring industry, one that has shared with the researcher important insights into its evolving community engagement and its development practices and considerations. The findings reveal that, in the implementation of South Africa's community renewables, government and companies dominate institutional work efforts in the stages of policy formulation and project development. But communities, the least informed and capacitated actor among the three, face the results and they have particular ways of responding, including corrective and disruptive ways. Reflective spaces are dominated by industry and strategically exclude communities from both asserting their experiences as well as from the opportunity to participate in creating collective understanding and agreeable processes that would foster the long-term relationship between company and community. This is a shortcoming that requires urgent attention to ensure positive institutional work and developmental impact.